Cyclic Voltammetric Behaviour and High-Performance Liquid Chromatography Amperometric Determination of Levamisole - Tsz Yan Joyce Chan; Kevin C. Honeychurch (Sci, 2024)
The electrochemical oxidation of levamisole, a glassy carbon electrode, was investigated over the pH range 2.0–10.0. Cyclic voltammetric investigations showed a single oxidation process was recorded, with a peak potential (Ep) shown to be pH-dependent in the range 5.0–8.0; between pH 2.0 and pH 5.0, and above pH 8.0, the Ep was found to be independent of pH, indicating apparent pKa values of 5.0 and 8.0. Peak currents were found to increase with increasing pH values. This voltammetric oxidation process was found to be consistent with a two-electron, two-proton oxidation to the corresponding sulfoxide. Based on these findings, the development of a of method based on the high-performance liquid chromatography separation of levamisole, with electrochemical detection being used for its determination, was explored. The chromatographic conditions required for the separation of levamisole were first investigated and optimized using UV detection. The conditions were identified as a 150 mm × 4.6 mm, 5 µm C18 column with a mobile phase consisting of 50% methanol, and 50%, 50 mM, pH 8.0 phosphate buffer. The technique of hydrodynamic voltammetry was applied to optimize the applied potential required for the determination of levamisole, identified as +2.3 V versus a stainless-steel pseudo-reference counter-electrode. Under the optimized conditions, levamisole exhibited a linear response of 1.00–20 mg/L (R2 = 0.999), with a detection limit of 0.27 mg/L. The possibility of determining levamisole in artificial urine was shown to be possible via simple dilution in the mobile phase. Mean recoveries of 99.7%, and 94.6%, with associated coefficients of variation of 8.2% and 10.2%, respectively, were obtained for 1.25 µg/mL (n = 5) and 2.50 µg/mL (n = 5).